At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

f(x)= 2x²-3x²+1 find f(3)​

Sagot :

Answer:

Step-by-step explanation:

f(3)=2*3^2 - 3*3^2 + 1

=2*9 - 3*9 + 1

=18-27+1

=19-27

=-8

S1NGH

Answer:

f ( 3 ) = -8

Step-by-step explanation:

→ Substitute x = 3 into 2x² - 3x² + 1

2 × ( 3 )² - ( 3 × ( 3 )² ) + 1

→ Simplify

-8

Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.